Politics of the female body : postcolonial women writers of the Third World - Katrak, Ketu H. (Rutgers University Press, 2006)
Is it possible to simultaneously belong to and be exiled from a community? Arguing that it is possible, the author uncovers the ways that the female body becomes a site of both oppression and resistance. She reveals common political and feminist alliances across geographic boundaries.